Olhares sobre o corpo-idoso praticante de hidroginástica em um programa de extensão - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This research aims to analyze the reasons why older people practice water aerobics at PIFPS / FEFF / UFAM, emphasizing the meaning of this practice in their lives. To carry out this research a bibliographical review and a field research proper were performed. In the bibliographic review, an in-depth analysis of the evolution of the body of the elderly over the ages was conducted, based on historical facts of Western society. Subsequently, the focus was on the body of the elderly and physical exercises, channeling to the so acclaimed by the elderly the water aerobics modality, going through the motivation and ending with the exposure on UnATI and PIFPS. The field research was carried out with 16 seniors who practiced water aerobics at PIFPS from 2018/1 to 2018/2 during the morning shift on Tuesdays and Thursdays from 08h to 09h, at UFAM / FEFF, Manaus / AM As a research instrument, a structured interview was used to interpret and understand the reports from the Content Analysis: technique of elaboration and analysis of units of meaning. The results found in the first question showed more recurrence that the human body is a "machine that needs care", but others stated that the human body is "spirituality". In the second question, the unanimous recurrence was that the primary factor for practicing water aerobics in PIFPS was “Health and disease”. Finally, the 3rd question answered “Socialization” and the gain of “Muscle Strength / Power” are recurrence items for modification in the body and life of the elderly. It was concluded that the body for the interviewed elderly has a concrete and abastrous characteristic, because besides having a mechanical characteristic and also has a transcendental characteristic. The reason for the practice of water aerobics is very recurrent in the life of the elderly, health and disease, which are a strong motivation for other processes that lead the individual to have quality of life, besides the practice of physical exercises such as water aerobics. It is known that the elderly practitioner of some form of exercise improves muscle strength and power, however socialization is a hallmark of water aerobics practice, because it creates unimaginable bonds between people in this phase of life.
Looks on the body-elderly practitioner of water aerobics in an extension program
Keywords: Exercícios físicos aquáticos; Exercícios físicos para idosos; Esportes para idosos; Idosos - Saúde mental; Educação física para idosos; CIÊNCIAS DA SAÚDE; Corpo; Idosos; Hidroginástica; Motivação